2010
DOI: 10.4194/trjfas.2010.0418
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Black Sea waters remain heavily impacted by a number of pollutants originating from different sources such as direct and indirect discharge of land based pollutants, sewage etc. The Black Sea environment is highly contaminated in many urban and industrialized areas of the many countries, resulting in severe ecotoxicological impacts. Heavy metals are toxic substances that accumulate in food chains with the increasing concentrations. In this review, heavy metal pollution in water column and sediment, with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…Zn is an abundant element and is Bat et al, 2009 andBoran andAltınok, 2010). found in most rocks and sediment. Studies on copper were quite variable throughout the catchment and seem to be significantly different between sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn is an abundant element and is Bat et al, 2009 andBoran andAltınok, 2010). found in most rocks and sediment. Studies on copper were quite variable throughout the catchment and seem to be significantly different between sites.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, studies on heavy metal in aquatic organisms should be conducted over a longer period before making any decision. Bat et al, 2009 andBoran andAltınok, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(Türkmen et al, 2008). Boran and Altinok (2010) concluded that heavy metal pollution in living organisms of the Black Sea has attracted considerable research attention since last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Coastal pollution has been increasing significantly over the recent years and found expanding environmental problems in many developing countries. Urban and industrial activities in coastal areas introduce significant amount of trace metals into the marine environment, causing permanent disturbances in marine ecosystems, leading to environmental and ecological degradation and constitute a potential risk to a number of flora and fauna species, including humans, through food chains (Boran, Altınok, 2010).…”
Section: Introductionmentioning
confidence: 99%